PERLINDUNGAN HAK CIPTA ATAS FORMAT PROGRAM TELEVISI - Eka Putri Ari, Putu; Dyah Satyawati, Ni Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
The paper entitled " Copyright Protection Program Format On TV " . Themethod used in this paper is the analysis of normative and regulatory approaches andconcepts approach. Analysis of the legal materials that have been obtained done bydescriptive, analytical, and argumentative. Television programs is a form of creation isdetermined by the idea. General Explanation of Act Number 19 of 2002 statesCopyright protection is not given to the idea or ideas. So the television programexperienced vacancies norm However, if researched article 12 paragraph ( 1 ) letter a,it will be found that the Act Number 19 of 2002 provides protection against thetypographical arrangement (layout ) of a published work . Changable (lay out) paperhas similarities with the television program formats. So it is possible to do the aboveinterpretation of Article 12 paragraph (1) letter a of Law Number 19 of 2002 to declarethat the format of the television program also got Copyright protection because it hassome similarities with the typographical arrangement (layout) papers.
Keywords: Copyright, Format, Program On TV